Elements of Creating a Positive Body Image from the View of Emerging Adulthood - Ahmet Kara; Ali Eryılmaz (Anı Publishing, 2018)
The aim of this research is to examine the positive body image in depth, based on the perceptions of emerging adulthood In this research, it was conducted in an descriptive phenomenological pattern as it was aimed to examine how emerging adulthood understand and perceive the positive body image concept. Eight consenting emerging adulthood attending the study attended undergraduate studies in various branches of the Education Faculty. The data were collected through semi-structured interviews with participants. Data analysis was carried out by a content analysis. According to the results of the analysis, four themes have been reached: "protection of body", acceptance of body, meaningfulness of body "and" positive emotion of body ". Emerging adulthood who stated that what their activities are that make their bodies feel good in terms of body protection are what they are. In the body of acceptance, they have positively perceived their bodies. They expressed their positive feelings towards their bodies as a result of experiences they experienced about their bodies in terms of positive emotions. Finally, they explain how the body meaningfulness its bodies in terms of meaning. Findings of this research can be used in individual or group counseling processes for emerging adulthood who have a body image problem. For example; The body images can be brought to a positive point by making activities to protect the body, to accept the body, to give meaning to the body and to develop a positive affect on the body.